Student Character Development Through Scouting Activities at MTS Alkhairaat Pusat Palu - Widayati Pujiastuti; Imran; Zuzan T Bachmid (Tadulako Social Science and Humaniora Journal, 2024)
The purpose of the study was to determine and describe the ability of Scoutmaster teachers to foster student character through Scouting activities at MTs. Alkhairaat Pusat Palu. The subjects in this study were 8 people consisting of 6 seventh-grade students, namely 3 male students and 3 female students who participated in Scouting activities, 1 Scout coach teacher, and 1 Deputy Principal. The type of research conducted is based on descriptive qualitative methods, the techniques used to collect data are observation, interviews, and documentation. Based on the study results, show that Student Character Development through Scouting Activities at MTs. Alkhairaat Palu Center, namely: 1) Responsibility Character 2) Discipline 3) independence.